Pandemic COVID-19 Joins History’s Pandemic Legion - David M. Morens; Peter Daszak; Howard Markel; Jeffery K. Taubenberger (mBio, 2020)
ABSTRACT With great apprehension, the world is now watching the birth of a novel pandemic already causing tremendous suffering, death, and disruption of normal life. Uncertainty and dread are exacerbated by the belief that what we are experiencing is new and mysterious. However, deadly pandemics and disease emergences are not new phenomena: they have been challenging human existence throughout recorded history. Some have killed sizeable percentages of humanity, but humans have always searched for, and often found, ways of mitigating their deadly effects. We here review the ancient and modern histories of such diseases, discuss factors associated with their emergences, and attempt to identify lessons that will help us meet the current challenge.